SISTEM PENYAMPAIAN JASA PENDIDIKAN - Didin Sirojudin; M. Dzikrul Hakim Al-Ghozali (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2020)
Providers of educational services are part of marketing management. Marketing management for educational institutions (in schools, especially madrasah) is needed in line with the increasingly attractive competition between schools. Marketing is needed for educational institutions to build a positive image. If the institution or school has a good image in the eyes of the community, it is likely that it will be easier to overcome competition. Judging from its type, this research is a case study, data collection methods, namely: (1) Observation (2) interviews (3) documentation. Furthermore, the data obtained and collected from field activities and qualitative analysis with data grouping techniques, then conclusions are drawn. The results of research on educational service delivery / marketing systems carried out by MIN 2 Jombang are: using internal marketing (internal marketing), external marketing and interactive marketing.